Über eine Klasse partieller Differentialgleichungen. II - Neniškytė, E. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Е. К. Ненишките. Об одном классе решений дифференциальных уравнений в частных производных. IIE. Neniškytė. Apie vieną diferencialinių lygčių dalinėmis išvestinėmis sprendinių klasę. II